Genetic analysis of yield and leaf curl virus resistance in chilli (Capsicum spp.) - Anandhi K (Department of Plant Breeding, College of Agriculture, 2010)
Pepper fruits (Capsicum spp.) are among the most consumed vegetables as fresh green or red and dried whole or ground forms in the world for its pungency. Leaf curl virus is an important biotic stress transmitted by the vector, Bemisia tabaci. Controlling the vector can be the only way to manage the disease and results in only partial control of disease. The incidence of disease is more in summer season and makes the cultivation uneconomical. There is an immediate need to develop leaf curl resistant varieties especially for summer cultivation. Hence the present investigation was undertaken at the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani during 2007-2009 with the objective of estimating the combining ability, heterosis and gene action involved in the inheritance of yield and leaf curl virus resistance. Five resistant C. frutescens accessions Mangalapuram Local, Thavanur Local, Kayamkulam Local, Mavelikkara Local and Nenmara Local were crossed in L x T pattern with three high yielding susceptible varieties Jwalamukhi, Jwalasakhi and Vellayani Athulya and 15 F1s were produced and evaluated along with the parents in randomized block design. Analysis of variance revealed highly significant genotypic difference for all the characters studied. The observations recorded were plant height (cm), number of branches, number of days to first flowering, plant spread (cm), duration of flowering (fruiting span), number of fruits per plant, fruit length (cm), fruit width (cm), pedicel - fruit ratio, fruit colour at intermediate stage, green fruit yield per plant (g), average fruit weight (g), number of seeds per fruit, hundred seed weight (g), duration of crop, vector population and virus disease scoring. Higher estimates of PCV and GCV were recorded for vulnerability index and green fruit yield per plant. High heritability coupled with high genetic advance were exhibited for days to first flowering, duration of flowering, number of fruits per plant, green fruit yield per plant, number of seeds per fruit, duration of crop and vulnerability index. Combining ability analysis showed that the line Mavelikkara Local and Nenmara Local were alone good general combiners for fruit yield along with leaf curl resistance. Four hybrids viz., Mavelikkara Local x Jwalasakhi, Nenmara Local x Vellayani Athulya, Kayamkulam Local x Jwalamukhi and Thavanur Local x Jwalamukhi exhibited significant sca effect for fruit yield. Considering per se performance, standard heterosis and sca effect two hybrids Mavelikkara Local x Jwalasakhi and Nenmara Local x Vellayani Athulya were found to be superior. Generation mean analysis was carried out using six-parameter model. Six generations viz. P1, P2, F1, F2, B1, B2 were built up among the crosses Mavelikkara Local x Jwalasakhi and Nenmara Local x Vellayani Athulya. Presence of additive, dominance and epistatic interaction for all the characters indicated that hybridization or recombination-breeding programme can be followed for future breeding.